Performance analysis of decentralized sewage solutions for multifamily residential condominiums in Aracaju - Conceição, Matheus Carvalho; Mendonça, Luciana Coêlho; Albuquerque, Tatiana Máximo Almeida (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The adoption of decentralized sewage treatment systems appears as an alternative for regions lacking sanitary infrastructure. Regarding Brazilian municipalities, they presented, in 2020, a sewage collection service rate for the urban population equal to 63.2%. Also, according to data from the National Sanitation Information System, in the municipality of Aracaju, capital of the state of Sergipe, the rate of collection of generated sewage is only 53.5%. Due this reality, investment in individual effluent treatment systems becomes a valuable alternative for areas that lack of sanitary infrastructure. In this work, the performance of domestic sewage treatment systems, used as individual treatment solutions in two multifamily condominiums in the capital of Sergipe, was evaluated. Physical-chemical monitoring of the individual sewage treatment systems was carried out, and the results indicated negative efficiencies in most of the analyzed parameters. As for the requirements of the current environmental legislation for the release of effluents, there was non-compliance with the legislation in almost all the time of observation. The lack of systems operation supervision by public agencies leads to failures that cause degradation of groundwater and surface water. Moreover, there is a lack of commitment to inspections and maintenance of the systems by those responsible for the condominiums. According to the types of solutions adopted, treated sewage with higher quality should be achieved and, thus, effluents with high loads of pollutants would not be released into water bodies.